2010
DOI: 10.2136/sssaj2009.0319
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Subsurface Flow in Hillslope and Stream Bank Erosion: A Review

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
170
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(176 citation statements)
references
References 73 publications
3
170
0
3
Order By: Relevance
“…The seepage from the subsurface flow to the stream channels unlike earlier application of the model (Tilahun et al, 2013a), base and interflow have a small sediment concentration early in the rainy phase (Fox et al, 2007;Fox and Wilson, 2010;Tebebu et al, 2010).…”
Section: Ped's Sediment Modulementioning
confidence: 77%
“…The seepage from the subsurface flow to the stream channels unlike earlier application of the model (Tilahun et al, 2013a), base and interflow have a small sediment concentration early in the rainy phase (Fox et al, 2007;Fox and Wilson, 2010;Tebebu et al, 2010).…”
Section: Ped's Sediment Modulementioning
confidence: 77%
“…The mechanism of the impact of soil moisture content on soil erosion has yet to be fully understood but studies have reported the influence of subsurface seepage forces on soil stability and the decrease of critical shear stress [58,60,62]. These forces can cause side walls to slide and channel to meander.…”
Section: Factors Affecting Ephemeral Gully Erosionmentioning
confidence: 99%
“…The soil-water pressure, seepage gradient forces, and the soil particle movement in relation to seepage erosion were the focus of previous studies [1,2]. Among these factors, seepage erosion is the predominant failure mechanism causing incidents in dams and streambanks [3,4], being responsible for approximately 50% of the failures [5,6].…”
Section: Introductionmentioning
confidence: 99%